A Camp in nursery land a collection of 20 favourite nursery rhymes - Wadia, Farzan; Christopher; Akshay; Excel Production (Firm); Excel Home Video (Firm) (Mumbai Excel Production Distributed by Excel Home Video, 2000)
jack and Jill, Hokey Pokey, Here we go round the melberyyy bush
Title from cassette label.
Christopher, Dhruv, Natasha, Paloma, Sakina, Zoher, Zendin, Jordan, Alisha, Malika, Akshay, Rhea, Nishita, Pooja, Ramona and Sarrah
Dolby digital 5.1, aspact ratio 1.78.1, format DVD 5 Single Layer sided disc, hi-fi stereo.
English
Keywords: Animated films; Children's films; Video recordings for the hearing impaired